Diversifying the industry’s customer base by developing dementia-friendly tourism destinations and tailored hospitality services - Wen, Jun; Zhang, Qin; Zheng, Danni; Hu, Fangli (Research in hospitality management, 2025)
Diversifying the hospitality industry’s customer base beyond typical healthy travellers will be important for the long-term viability and success of the industry. This viewpoint advocates for interdisciplinary efforts focusing on dementia and tourism to lay a solid foundation to create visitor-friendly tourism destinations with suitable hospitality services for travellers with specific ailments. In spite of some preliminary work, interdisciplinary dementia-oriented research bridging tourism and healthcare fields is in its infancy. Convincing evidence of how and to what extent tourism can help people with dementia is lacking. Thus, despite the academic literature introducing the concept of dementia-friendly tourism destinations, no such options presently exist. This viewpoint critically identifies the knowledge gaps that have impeded progress toward the development of dementia-friendly tourism destinations. Hospitality services are an essential component of positive tourism experiences, and certain dementia-friendly services are proposed to support truly dementia-friendly tourism destinations that will expand the customer base for tourism and hospitality industries at these tailored destinations.